Salomania and the Representation of Race and Gender in Modern Erotic Dance - Devereux, Cecily Margaret, 1963- (Book collections on Project MUSE., 2023)
"This is a study of the performance and circulation of the figure of Salome in imperial Europe and settler colonial North America during the late years of the long period of expansion and territorial occupation at the end of the nineteenth century and the beginning of the twentieth. The book opens with a discussion of Maud Allan's "The Vision of Salome" dance on the London stage in 1908, and the resulting "Salomania" craze that dominated dance for years and pervaded innumerable works in all media that followed. This is followed by a history of erotic dance as it emerged in the nineteenth century, then turns to the representation of Salome in art and literature, in works by writers Gustave Flaubert and Oscar Wilde, composer Richard Strauss, and film director Billy Wilder, as well as the dance interpretations by Allan and Loie Fuller. The book arrives at the phenomenon of "Salomania" as a turning point in the history of erotic dance, reconsidering this event as one that is grounded in the cultural logic of reproductive fetishism shaped by the male artists of the later nineteenth century and that is best understood as a series of interrelated performances in which reproductivity itself is central."--